KEMAMPUAN MENULIS TEKS PROSEUR SISWA KELAS VII SMP NEGERI 4 TAEBENU KABUPATEN KUPANG TAHUN PEMBELAJARAN 2024/2025 - Eni Sitriana Kase; Karus Margareta; Dian Sari Pekuwali (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
The focus of this research is adjusted to the formulation of the problem discussed in the study, namely how is the ability to write procedural texts for class VIII A students of SMP Negeri 8 West Sabu. There are two aspects, namely, (1) The structure of the text is divided into (Goals, Steps, Reaffirmation). (2) The linguistic rules are divided into (command verbs, persuasive statements, conjunctions and adverbs). The theory used in this study is the theory of writing is a communication activity in the form of delivering messages (information) in writing to parties using written language as a tool or medium. The method used is qualitative research, one of the research procedures that results in the writing or behavior of students being observed. Based on the average score obtained by the class in the structure of the procedure text, there are 9 students with code names AB, DAS, DK, GJB, IN, MAT, NAO, PST, RDR having very good categories, there are 6 students with code names of students AAB, AA, FJT, GMA, MZB, MAO have good categories, there is 1 person with the code name of the TRB student in the fairly good category, there are 4 people with the student code name AB, DAS, DSM, GMA, GJB, MAT, MZB, YMGS, SAD who have a poor category. From various aspects in the structure of the text above, there are 16 students who complete and 4 students who do not complete. Based on the average score obtained by the class using linguistic rules, there are 2 students with code names of GM students, LMR has a very good category, there are 8 students with code names of students AFM, AHD, KKL, DAR, JDT, KPT, MRL, MDM have good category, there is 1 person with the code name of the DKK student in the fairly good category, there are 9 people with the student code name AVR, BRK, CJD, EHR, FKH, IL, JL, RHW, SAD who have a poor category. Based on the linguistic rules, there were 11 students who completed and 9 students who did not complete. So, the number of students who completed based on the structure of the text and linguistic rules were 14 students, and students who did not complete. This shows that the ability of class VII students of state junior high school 4 Taebenu, Kupang regency 2024/2025 learning academic year in writing procedure texts in accordance with the text structure and linguistic rules has reached (KKM) 75.